The Arab Awakening : Islam and the New Middle East - Tariq Ramadan (London Allen Lane, 2012)
The author is one of the most acclaimed figures in the analysis of Islam and its political dimensions today. In this book, he explores the opportunities and challenges across North Africa and the Middle East, as they look to create new, more open societies.
Includes Notes
Keywords: Democratization